Avaliação do desempenho de estações de tratamento de esgoto para fins de reúso da água - Santos, Luciene da Silva (2018)
This study evaluated the performance of 19 sewage treatment plants in the State of Mato Grosso do Sul, Brazil, from different treatment technologies, in order to evaluate the reuse potential of the treated effluent. An economic feasibility study was also carried out on the reuse of treated effluents from the State WWTP. Currently, the reuse of water has been applied in industry, in the clearing of rainwater or sewage networks, cleaning of public roads, irrigation of beds, among other non-potable purposes. Therefore, the objective of this study is to understand the relationship between sizing and operation parameters, seeking the most efficient arrangements for the proposed reuse of treated effluent. The mean performance of WWTP was lower than expected for treatment technologies, considering the analyzes used in the study. However, promising results were obtained by some WWTP, which demonstrates that the limitations are not only of the treatment processes, but can also originate from eventual system design, operation and maintenance problems. Results indicate that the practice of water reuse significantly improves the return period of the investment in the universalization of the sanitary sewage service in the municipalities of the State of Mato Grosso do Sul, with averages of improvement of financial performance ranging from 10% to 15%, considering the most pessimistic scenario and the most optimistic scenario, respectively.